1992
DOI: 10.1007/bf00032981
|View full text |Cite
|
Sign up to set email alerts
|

A photoacoustic study of water infiltrated leaves

Abstract: Photoacoustic measurements of photosynthetic energy storage were conducted on water infiltrated pea and sugar maple leaves. The samples were vacuum infiltrated with pure water or with a suitable buffer. The use of such methodology permitted an accurate determination of the energy storage parameter at low modulation frequencies, where in non-infiltrated leaves oxygen evolution dominates the photoacoustic signal and does not allow energy storage measurements. Differences between infiltration media were not essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The existence of cyclic electron transport in vivo in C 3 plants has also been questioned by photoacoustic measurements in far-red light (Herbert et al, 1990), which allow a direct and quantitative measure of energy storage (ES) by cyclic electron flow around PS I (for review, see Malkin and Canaani, 1994). This method has confirmed the existence of cyclic electron transfer reactions in C 4 plants, algae, and cyanobacteria (Herbert et al, 1990), but failed to show significant cyclic activity in C 3 plant leaves (Herbert et al, 1990;Havaux et al, 1991;Malkin et al, 1992).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The existence of cyclic electron transport in vivo in C 3 plants has also been questioned by photoacoustic measurements in far-red light (Herbert et al, 1990), which allow a direct and quantitative measure of energy storage (ES) by cyclic electron flow around PS I (for review, see Malkin and Canaani, 1994). This method has confirmed the existence of cyclic electron transfer reactions in C 4 plants, algae, and cyanobacteria (Herbert et al, 1990), but failed to show significant cyclic activity in C 3 plant leaves (Herbert et al, 1990;Havaux et al, 1991;Malkin et al, 1992).…”
mentioning
confidence: 92%
“…In higher plants, photoacoustic measurements must be conducted on water-or buffer-infiltrated leaves to eliminate the oxygen-evolution-related component of the photoacoustic signal (Malkin et al, 1992). In infiltrated leaves of maize (a C 4 plant), ES in far-red light (approximately 15%) was close to the activity measured in Synechocystis sp.…”
Section: Cyclic Electron Transport Around Ps I In Different Organismsmentioning
confidence: 99%
“…This point has been a matter of debate in the last decade given that direct measurements of cyclic electron flow such as those given by photoacoustic experiments failed to detect any significant activity in C 3 plants (Heber and Walker, 1992;Bendall and Manasse, 1995). Using photoacoustic measurements on peas, Malkin et al (1992) measured a weak cyclic activity, saturating at low-light intensity. In the same way, based on measurements of P700 rereduction, chlorophyll fluorescence, and light scattering on spinach, Heber et al (1995a) concluded to low cyclic activity in C 3 plants, mainly restricted to the control of PSII, taking part in the complex machinery that acts to protect the photosynthetic apparatus against photo-inhibition.…”
Section: Involvement Of the Ndh Complex In Cyclic Electron Flow Arounmentioning
confidence: 99%
“…Photoacoustic measurements, which allow a direct and quantitative measurement of energy storage by cyclic electron flow around PSI in vivo, have been used to show the existence of cyclic electron transfer reactions in C 4 plants, algae, and cyanobacteria (Herbert et al, 1990). However, until now, this technique failed to show significant cyclic activity in C 3 plants (Herbert et al, 1990;Malkin et al, 1992). For the unicellular alga Chlamydomonas reinhardtii, Ravenel et al (1994), by studying the effect of antimycin A and of different inhibitors on photoacoustic measurements, proposed that two pathways are operating in vivo around PSI.…”
mentioning
confidence: 99%
“…When the plastic film was not used, leaf discs were soaked for 3 h in an osmoticum buffer (25 mm phosphate buffer, pH 7.0, 200 mm sorbitol, 10 mm KCl, and 2 mm MgCl 2 ) to eliminate the photobaric component of the photoacoustic signal as described by Malkin et al (1992). Synechocystis sp.…”
Section: Photoacoustic Measurements Of Photochemical Esmentioning
confidence: 99%